The Abuse of Sympathetic Power to Counter Hegemony - S. Andika Cahya Ari Wibowo; Dwi Rukmini (English Language and Literature International Conference (ELLiC) Proceedings, 2018)
Sympathy may be generally defined as a support given to other who is believed that he/she is undeservedly suffering or misfortune. Identical to the positive notion of „support‟, the practice of sympathy in the society portrays deviating purpose. Powerless can effectively appeal to the sympathy of their counterparts for their own strategic gain, and more specifically, that this powerless individuals can leverage their weaknesses through the strategic use of sympathy in order to mitigate the disadvantages of lacking power. This powerless strategy may even be used to maintain their relation with the powerful. It calls sympathy as means of resistance. These phenomena will be noted as the abuse of sympathetic power. This article is intended to explore the practice of sympathetic power to counter hegemony. It attempts to portray the sympathetic power‟s potency as means of resistance to counter hegemony. The area of inquiry constricted into the specified context of Minah‟s Cocoa Beans Stealing Case in 2009. The study will be conducted by combining Fairclough‟s CDA model with Systemic Functional Linguistics (SFL), particularly by considering interpersonal metafunction proposed by Halliday. Based on the analysis, Minah appeals sympathy by exposing her innocence and all the characteristics that she naturally possess. She was able to influence court decision to set her free even all the evidences prove her for commiting the crime of stealing.